Receptor for complement peptide C3a: a therapeutic target for neonatal hypoxic‐ischemic brain injury. Issue 9 (4th June 2013) - Järlestedt, Katarina; Rousset, Catherine I.; Ståhlberg, Anders; Sourkova, Hana; Atkins, Alison L.; Thornton, Claire; Barnum, Scott R.; Wetsel, Rick A.; Dragunow, Mike; Pekny, Milos; Mallard, Carina; Hagberg, Henrik; et al.
Abstract : Complement is an essential component of inflammation that plays a role in ischemic brain injury. Recent reports demonstrate novel functions of complement in normal and diseased CNS, such as regulation of neurogenesis and synapse elimination. Here, we examined the role of complement‐derived peptide C3a in unilateral hypoxia‐ischemia (HI), a model of neonatal HI encephalopathy. HI injury was induced at postnatal day 9 (P9), and loss of hippocampal tissue was determined on P31. We compared WT mice with transgenic mice expressing C3a under the control of glial fibrillary acidic protein promoter, which express biologically active C3a only in CNS and without the requirement of a priori complement activation. Further, we injected C3a peptide into the lateral cerebral ventricle of mice lacking the C3a receptor (C3aR) and WT mice and assessed HI‐induced memory impairment 41 d later. We found that HI‐induced tissue loss in C3a overexpressing mice was reduced by 50% compared with WT mice. C3a peptide injected 1 h after HI protected WT but not C3aR‐deficient mice against HI‐induced memory impairment. Thus, C3a acting through its canonical receptor ameliorates behavioral deficits after HI injury, and C3aR is a novel therapeutic target for the treatment of neonatal HI encephalopathy.—Järlestedt, K., Rousset, C. I., Ståhlberg, A., Sourkova, H., Atkins, A. L., Thornton, C., Barnum, S. R., Wetsel, R. A., Dragunow, M., Pekny, M., Mallard, C., Hagberg, H., Pekna, M., Receptor for complement peptide C3a: a therapeutic target for neonatal hypoxic‐ischemic brain injury. FASEB J. 27, 3797–3804 (2013). www.fasebj.org